2009
DOI: 10.1002/art.25019
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia is a risk factor in the progression of carotid intima‐media thickness in juvenile‐onset systemic lupus erythematosus

Abstract: Objective. To characterize the atherosclerotic risk factors in the progression of subclinical atherosclerosis in patients with juvenile-onset systemic lupus erythematosus (SLE).Methods. This was a longitudinal study of 76 patients with juvenile-onset SLE. Carotid arteries were evaluated using ultrasonography at baseline and at followup visits at 6-month intervals over the 6-year study period. Clinical and laboratory parameters, disease activity, treatment, and traditional risk factors for atherosclerosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
5
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 41 publications
3
26
5
4
Order By: Relevance
“…Most of them were benign, limited and without postherpetic neuralgia. 38 leukopenia on SLE diagnosis, lymphopenia on SLE diagnosis, higher creational level, CRP >5 mg/l were positively associated with progression of intima-media thickening by univariate analysis. (p ¼ 0.027, 0.006, 0.037 and 0.048, respectively).…”
Section: Varicella-zoster Virus Infectionmentioning
confidence: 96%
“…Most of them were benign, limited and without postherpetic neuralgia. 38 leukopenia on SLE diagnosis, lymphopenia on SLE diagnosis, higher creational level, CRP >5 mg/l were positively associated with progression of intima-media thickening by univariate analysis. (p ¼ 0.027, 0.006, 0.037 and 0.048, respectively).…”
Section: Varicella-zoster Virus Infectionmentioning
confidence: 96%
“…This hypothesis is raised because of previous reports indicating that leukopenia is associated with atherosclerosis in SS (1) and that lymphopenia is associated with atherosclerosis in SLE (2). Their study also reveals that anti-SSA antibodies are a risk factor for the progression of atherosclerosis, and data from SLE studies showed that lymphopenia is highly associated with the presence of anti-SSA antibodies (3).…”
Section: To the Editormentioning
confidence: 94%
“…There were no differences in the baseline carotid IMT between patients with and those without (mean Ϯ SD 0.62 Ϯ 0.07 versus 0.64 Ϯ 0.09; P ϭ 0.26). Furthermore, we used the generalized estimating equation (GEE) method to analyze the correlation between the anti-SSA antibody data and the progression of atherosclerosis (2). Progression of IMT was not associated with the presence of anti-SSA antibodies (P ϭ 0.93) in univariate analysis.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The role of SLE activity in the formation of non calcified coronary plaque (NCP) was investigated by Kiani et al; unlike coronary calcium, which is not associated with SLE activity measures or with active serologies, NCP is more common in patients with active disease (Kiani, Vogel-Claussen et al 2010). Additionally, the presence of lymphopenia and higher levels of serum creatinine and CRP seem to be disease related risk factors in the progression of carotid IMT in juvenile-onset SLE as demonstrated by Huang et al (Huang, Chung et al 2009). In particular, lupus EPCs/CACs (myeloid circulating angiogenic cells) have decreased capacity to differentiate into mature ECs and synthesize decreased amounts of the molecules vascular endothelial growth factor and hepatic growth factor (Rajagopalan, Somers et al 2004;Denny, Thacker et al 2007;Lee, Li et al 2007;Moonen, de Leeuw et al 2007;Westerweel, Luijten et al 2007).…”
Section: Slementioning
confidence: 99%